Intraoperative fluorescence imaging to localize tumors and sentinel lymph nodes in rectal cancer. Issue 1 (2nd January 2016) - Handgraaf, Henricus J.M.; Boogerd, Leonora S.F.; Verbeek, Floris P.R.; Tummers, Quirijn R.J.G.; Hardwick, James C.H.; Baeten, Coen I.M.; Frangioni, John V.; van de Velde, Cornelis J.H.; Vahrmeijer, Alexander L.
Abstract: Tumor involvement at the resection margin remains the most important predictor for local recurrence in patients with rectal cancer. A careful description of tumor localization is therefore essential. Currently, endoscopic tattooing with ink is customary, but visibility during laparoscopic resections is limited. Near-infrared (NIR) fluorescence imaging using indocyanine green (ICG) could be an improvement. In addition to localize tumors, ICG can also be used to identify sentinel lymph nodes (SLNs). The feasibility of this new technique was explored in five patients undergoing laparoscopic low anterior resection for rectal cancer. Intraoperative tumor visualization was possible in four out of five patients. Fluorescence signal could be detected 32±18 minutes after incision, while ink could be detected 42 ± 21 minutes after incision (p = 0.53). No recurrence was diagnosed within three months after surgery. Ex vivo imaging identified a mean of 4.2 ± 2.7 fluorescent lymph nodes, which were appointed SLNs. One out of a total of 83 resected lymph nodes contained a micrometastasis. This node was not fluorescent. This technical note describes the feasibility of endoscopic tattooing of rectal cancer using ICG:nanocolloid and NIR fluorescence imaging during laparoscopic resection. Simultaneous SLN mapping was also feasible, but may be less reliable due to neoadjuvant therapy.